2016
DOI: 10.3389/fmicb.2016.00363
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Metabolic Potentials of Subsurface Crustal Microorganisms from the Western Flank of the Mid-Atlantic Ridge

Abstract: Deep-sea oceanic crust constitutes the largest region of the earth’s surface. Accumulating evidence suggests that unique microbial communities are supported by iron cycling processes, particularly in the young (<10 million-year old), cool (<25°C) subsurface oceanic crust. To test this hypothesis, we investigated the microbial abundance, diversity, and metabolic potentials in the sediment-buried crust from “North Pond” on western flank of the Mid-Atlantic Ridge. Three lithologic units along basement Hole U1383C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 122 publications
2
36
0
Order By: Relevance
“…An average of 200 fields of view were counted for each membrane. The area of each field of view was set at 10,000 m 2 , and the detection limit was ϳ10 3 cells/ml for a 95% probability of detecting at least 1 cell, as described previously (21,22). The blank control was performed with autoclaved and 0.2-m-pore-size mesh membrane-filtered Milli-Q water (18.2 M⍀; Millipore, USA) and processed with the same filtration and staining steps as the bacterial samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An average of 200 fields of view were counted for each membrane. The area of each field of view was set at 10,000 m 2 , and the detection limit was ϳ10 3 cells/ml for a 95% probability of detecting at least 1 cell, as described previously (21,22). The blank control was performed with autoclaved and 0.2-m-pore-size mesh membrane-filtered Milli-Q water (18.2 M⍀; Millipore, USA) and processed with the same filtration and staining steps as the bacterial samples.…”
Section: Methodsmentioning
confidence: 99%
“…Equimolar concentrations of each purified PCR product were pooled and sequenced on an Illumina HiSeq 2500 platform (2 ϫ 250 bp; Illumina, USA), according to standard protocols. Processing of raw sequence data was performed as described elsewhere (21). Briefly, raw reads which contained a 50-bp continuous fragment with an average quality score less than 30 and/or any ambiguities were removed.…”
Section: Enumeration Of Microbial Cells and Hemocytes In Hemolymph (mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies at this site have revealed diverse microbial communities with abundances of up to ϳ10 5 cells g Ϫ1 rock in the igneous crust (15,19,24). In addition, microbial nitrogen transformation occurs in the overlying sediments from the sediment-water interface down to the basement, resulting in a downward flux of nitrate into the underlying oceanic crust (25).…”
mentioning
confidence: 91%
“…Despite the potentially global importance of microbial life within the upper crust, fundamental questions regarding cellular recruitment, extent of activity, niche partitioning, and community succession in this habitat remain unanswered. There have been only a few published studies dedicated to microbial interrogation of native subseafloor crustal rocks (1,(14)(15)(16)(17) and even fewer that have addressed the potential biogeochemical functions of these communities (16,18). Based on the limited body of literature, it appears that microbial communities in the subseafloor crust are unique in comparison to those found in hydrothermal plumes, deep seawater, and hydrothermal fluids and in seafloor exposed basalt (12) and the overlying sediments (19).…”
mentioning
confidence: 99%